Continuous improvement CSF framework for assessing CI maturity in ISO and non-ISO certified construction contracting organizations - Hamid, Hashima (2015)
Continuous Improvement (CI) is being recognized as key enabler for productivity improvement within the construction industry especially since it was emphasized in the Egan Report in 1998. However, core business processes within the construction industry have not been able to take advantage of this philosophy. Research and development efforts in this area has been lacking in terms of its applications from a construction industry-specific perspective. Attempts to focus on CI through specific TQM and of recent ISO 9000:2000 efforts seem to have had little impact, especially complicated by the unique features of the temporary nature of construction project organizations. It has been identified that construction suffers from delays, cost overruns, rework, variations, claims, poor contract administration and lax supervision by the client’s representative. Taking into account that construction projects are unique, temporary and embedded in sub-contracting culture, the task of achieving productivity improvement requires addressing the CI of specific processes. Hence, the first objective of this research is to determine the Critical Success Factors (CSFs) for Continuous Improvement (CI) as a focused independent management tool in the Planning and Scheduling (P&S) of construction projects. 38 Success Factors of CI for P&S of construction projects from literature review were listed and verified using three rounds of Delphi Method This constituted the CI Maturity Assessment Framework that was used to assess ISO and Non-ISO construction organizations. The finding shows that, ISO certified companies exhibit a comparatively correlation with CI maturity level, however not being significant enough than non-ISO companies. Hypotheses testing used to compare both groups, and it was found that 35 out of 38 of the CSFs did not show any significant difference in CI maturity level. Hence, it cannot be claimed that ISO certified organizations fully practice the principles of CI. Finally, a conceptual framework for implementing CI based on The Kaizen Blitz approach is proposed for construction projects to enable rapid performance improvements over short timescales that is suitable considering the various construction projects peculiarities.